Chinese Historical Memory of the World War II: Points of Connection and Difference with the Russian View - Ivan Zuenko (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения)
Introduction. The article is devoted to the analysis of the Chinese historical memory of World War II, current trends in reassessing the role of the war in the history of China, and the participation of China and the Soviet Union in it (the history of the 88th separate rifle brigade of the Far Eastern Front was used as a case study). Methods and materials. For the collection of material on the 88th brigade, the author made a research trip to the Khabarovsk Territory (Vyatskoye village) in 2024, during which materials from the archive of the Grodekov Regional Museum, the file of the newspaper “Pacific Star,” stored in the Far Eastern State Scientific Library, were studied. Sources on Chinese historiography were collected in several stages: the textbooks examined were purchased on the open market during the author’s trip to the PRC; the studied scientific monographs are available by subscription in the Chinese scientific information database CNKI. Analysis. The author focuses his attention on those subjects in the history of cooperation between Russia and China during the war, which, under a certain set of circumstances, can be considered not as points of contact but points of divergence between the two countries. Results. In particular, trends are recorded towards expanding the chronology of the war between China and Japan from eight years to fourteen, “rebranding” World War II as the “World Anti-Fascist War,” and downplaying the role of the USSR in the liberation of Manchuria from the Japanese occupiers. At the same time, in the deepest conviction of the author, a compromise version of the common history, excluding falsification and infringement of the interests of Russia and China, is quite possible and can be developed as a result of intensified bilateral scientific discussion.